1996
DOI: 10.1177/153857449603000209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normovolemic Hemodilution on Fatal Postoperative Pulmonary Embolism in Major Elective Orthopedic Surgery. A Retrospective Analysis on 4653 Patients

Abstract: It has been suggested that the benefits of transfusion are currently greatly overrated, with physicians reflexively administering blood in the nearly unchallenged view that failure to transfuse would have dire consequences. As a matter of fact, the tolerability and safety of normovolemic anemia have been well documented for many years in several anesthesiologic settings. Objective: To assess the impact of normovolemic hemodilution on blood bank resources and in-hospital mortality in major elective orthopedic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Haemodilution, when it is not contraindicated and well tolerated by the patients also reduces the risk of thromboembolism (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemodilution, when it is not contraindicated and well tolerated by the patients also reduces the risk of thromboembolism (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on severe haemodilution have shown that correct organ perfusion and tissue oxygenation are guaranteed in the presence of normovolemia (8, 9). Intentional haemodilution is also of clinical efficacy in reducing thromboembolic risks (10)(11)(12) in consideration of hypercoagulable state (13) and in causing a peak of endogenous erythropoietin (EPO) levels (14).…”
Section: Introductionmentioning
confidence: 99%